Wahana Lestari: Bil 1 2020 / Perpustakaan Tun Dr. Ismail Cawangan Johor, UiTM Johor - Abdullah, Mawar Noor; Norudin, Nurul Amin; Mohd Nor, Roslan; Samsuri, Mohd Azmi; Mohd Azahar, Nor Azelea; Nurul Iza, Ibrahim (Perpustakaan Tun Dr Ismail, UiTM Johor, 2020)
ASSALAMUALAIKUM